Information Needs of Hearing Impaired Students: A Case Study of Government VHSS for Deaf, Thiruvananthapuram - Midhula Soman, V. S.; Pillai Sudhier, K. G. (Journal of Information and Knowledge, 2015)
The study was conducted to investigate the information seeking behavior of hearing impaired students in school libraries. The study was based on a questionnaire survey and data was collected from students from Government Vocational Higher Secondary School (VHSS) for Deaf, Thiruvananthapuram. The analyses revealed that the information needs of hearing impaired students have become complex and problematic due to the insufficiency of adequate information sources and services and there are quite a number of challenges faced by the hearing impaired students in accessing information from the libraries. It has been found that, even though assistive technologies are playing a vital role in the educational aspects of differently-abled students, it is not playing a role in the progress in library services for differently-abled. Most of the students are not aware of the assistive technologies available to assist them in accessing information. The overall result of the study was that, though the library services provided in the school are useful for their studies, the respondents cannot make use of them because of barriers. The study comes out with some practical suggestions to improve the library facilities for hearing impaired students with the help of assistive technologies.